2021
DOI: 10.1111/lam.13462
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assays on the susceptibility of four species of nematophagous fungi to anthelmintics and chemical fungicides/antifungal drug

Abstract: Using nematophagous fungi for the biological control of animal parasitic nematodes will become one of the most promising strategies in the search for alternative chemical drugs. The purpose of this study was to check the in vitro activity of four anthelmintics, four chemical fungicides and two antifungal drugs on the spore germination of nematophagous fungi: Duddingtonia flagrans (SF170), Arthrobotrys oligospora (447), Arthrobotrys superba (435) and Arthrobotrys sp. (PS011). A modified 24-well cell culture pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…This suggests a remarkable difference in antifungal activity between the various substituent compounds. Compounds with promising antifungal activity were selected for calculation of the EC 50 value using a linear regression method 37 . As shown in Table 2, compound 18 displayed the lowest EC 50 of 1.37 μg ml −1 against S. sclerotiorum , the most powerful inhibitory effect on this pathogen among the selected compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests a remarkable difference in antifungal activity between the various substituent compounds. Compounds with promising antifungal activity were selected for calculation of the EC 50 value using a linear regression method 37 . As shown in Table 2, compound 18 displayed the lowest EC 50 of 1.37 μg ml −1 against S. sclerotiorum , the most powerful inhibitory effect on this pathogen among the selected compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds with promising antifungal activity were selected for calculation of the EC 50 value using a linear regression method. 37 As shown in Table 2, compound 18 displayed the lowest EC 50 of 1.37 μg ml −1 against S. sclerotiorum, the most powerful inhibitory effect on this pathogen among the selected compounds. Compounds 1, 2, and 18 possessed potent activity against the mycelial growth of B. cinerea with an approximate EC 50 value of 5.1 μg ml −1 , which was stronger than those of compounds 12 and 13, with EC 50 values of 7.04 and 10.78 μg ml −1 , respectively.…”
Section: Antifungal Activities Of 1-18 and Sar Analysismentioning
confidence: 97%
“…Although resistance is quickly developed to chemical drugs, they are more effective at killing nematodes than fungi, so the combination of the two could also reduce resistance and enhance nematicidal efficiency. Further studies are still needed to establish the pattern of combining NF with chemical drugs, such as the compatibility, appropriate dose, and time [104,106].…”
Section: Discussionmentioning
confidence: 99%
“…[107]. D. flagrans has been found to have high susceptibility to tested drugs, including fenbendazole, thiabendazole and ivermectin, carbendazim, and difenoconazole [106]. In vivo tests also confirmed that chemical drugs inhibited the activity of D. flagrans spores when used in combination with albendazole [108].…”
Section: Coadministration Of Fungi With Compoundsmentioning
confidence: 93%
See 1 more Smart Citation